Estrategias metodológicas de comprensión lectora para el desarrollo de la inteligencia lingüística de los estudiantes de cuarto año de educación general básica, de la escuela “Boyacá” parroquia San Gerardo, cantón Guano, provincia de Chimborazo, año lectivo 2013-2014 - Gusqui Gusqui, Norma Elizabeth (2016)
This research; It was a compendium of great importance for Basic Education. In conducting in-depth study of the problem it was raised overall objective Determining methodological reading comprehension strategies for the development of linguistic intelligence of the seniors of General Basic Education, school "Boyacá" Parroquia San Gerardo, Canton guano, Chimborazo Province, school 2013-2014. "this research is developed by the need to use reading comprehension strategies in children the fourth year of basic education School" Boyacá "San Gerardo parish. In this degree the limiting treatment to reading comprehension by the teacher known. There is the general and specific objective, among them are raised: to determine the influence of reading comprehension strategies to develop linguistic intelligence of children in the fourth year of basic education "Boyacá" School, parish San Gerardo, 2013-2014. To reach the achievement it was started from the analysis of a theoretical framework emphasizing the approach of the two variables with their respective sub-study. a hypothesis that it is checked by the proportional method was established. Regarding the methodological framework a non-experimental design was used because it was not manipulated any variable, the type of research was descriptive, exploratory and field so we can relate reading comprehension and development of linguistic intelligence; the method we used was the scientist who allowed guide all the work to get to the truth. General methods were inductive, deductive, analytical and synthetic method that is evident in each of the chapters. The technique was implemented was the observation that provided the same information required to find relevant findings, the instrument was the observation sheet with 10 items, the same that was valued by experts in science. Finally it came to the conclusion that reading comprehension helps develop linguistic intelligence in children; therefore it corresponds to seek methodological teaching strategies to use in the classroom and thus develop meaningful.